Optimal simple and implementable monetary and fiscal rules - Stephanie Schmitt-Grohé; Martín Uribe (Federal Reserve Bank of Atlanta, 2007)
This paper computes welfare-maximizing monetary and fiscal policy rules in a real business cycle model augmented with sticky prices, a demand for money, taxation, and stochastic government consumption. We consider simple feedback rules whereby the nominal interest rate is set as a function of output and inflation and taxes are set as a function of total government liabilities. We implement a second-order accurate solution to the model. We have several main findings. First, the size of the inflation coefficient in the interest rate rule plays a minor role for welfare. It matters only insofar as it affects the determinacy of equilibrium. Second, optimal monetary policy features a muted response to output. More importantly, interest rate rules that feature a positive response to output can lead to significant welfare losses. Third, the welfare gains from interest rate smoothing are negligible. Fourth, optimal fiscal policy is passive. Finally, the optimal monetary and fiscal rule combination attains virtually the same level of welfare as the Ramsey optimal policy.
Keywords: E52; E61; E63; 330; optimal fiscal and monetary policy; nominal rigidities; optimal inflation volatility; second-order approximation techniques; Regelgebundene Politik; Geldpolitik; Finanzpolitik; Wohlfahrtsanalyse; Wirtschaftsmodell